Effect of scarf repair geometry on the impact performance of aerospace composites - Shankar, Sridharan Vijay (2023)
This experimental study investigates the effect of scarf geometry in restoring the impact response of scarf-patched 3 mm thick glass-fiber reinforced polymer (GFRP) matrix composite laminates. Traditional circular along with rounded rectangular scarf patch configurations are considered repair patches. Experimental measurements revealed that the temporal variations of force and energy response of the pristine specimen are close to that of circular repaired specimens. The predominant failure modes were witnessed only in the repair patch which includes matrix cracking, fiber fracture, and delamination, and no discontinuity in the adhesive interface was witnessed. When compared with the pristine samples, the top ply damage size of the circular repaired specimens are larger by 9.91%, while that of the rounded rectangular repaired specimens is larger by 434.23%. The results show that circular scarf repair is a more suitable choice of repair approach under the condition of a 37 J low-velocity impact event even though the global force-time response is similar.